Stop, Question, and Frisk: A Tool of Racial Control in New York City - Evans, Justice D. (2019)
Broken Windows policing through the utilization of Stop, Question, and Frisk has been widely used by the New York City Police Department (NYPD) since the 1990s, as guaranteed by landmark Supreme Court Case Terry v. Ohio (1968). As a result, hundreds of minority citizens have been the victim of routine stops for minor offenses through this aggressive police tactic. This study utilizes 2017 NYPD Stop, Question, and Frisk Data to determine whether broken windows policing, through stop, question, and frisk, operates as a mode of racial control for African Americans in New York City. Through the utilization of chi-square analyses, binary logistic regression, and multi nominal logistic regression, statistically significant associations were found for several variables based on race